The impacts of neoadjuvant chemotherapy and of cytoreductive surgery on 10‐year survival from advanced ovarian cancer. Issue 3 (13th January 2021) - Kim, Soyoun Rachel; Kotsopoulos, Joanne; Sun, Ping; Bernardini, Marcus Q.; Laframboise, Stephane; Ferguson, Sarah E.; Rosen, Barry; Narod, Steven A.; May, Taymaa
Abstract: Objective: To compare the long‐term survival outcomes for women with advanced ovarian cancer treated with chemotherapy either before or after surgery (neoadjuvant chemotherapy vs primary cytoreductive surgery) at a single tertiary cancer center. Methods: Retrospective cohort study of 326 patients with Stage IIIC or IV high‐grade serous ovarian cancer who received neoadjuvant chemotherapy or primary cytoreductive surgery between 2001 and 2011. Clinical treatments were recorded and 10‐year survival rates were measured. Results: A total of 183 women (56.1%) underwent primary cytoreductive surgery and 143 women (43.9%) received neoadjuvant chemotherapy. Women who received neoadjuvant chemotherapy were more likely to have no residual disease than those who underwent primary cytoreductive surgery (51.4% vs 41.5%; P  = 0.030) but experienced inferior 10‐year overall survival (9.1% vs 19.3%; P  < 0.001). Among those who had primary cytoreductive surgery, those with no residual disease had superior 10‐year overall survival than those who had any evidence of residual disease (36.0% vs 7.2%; P  < 0.001). Conclusion: Among women with advanced ovarian cancer, those who underwent primary cytoreductive surgery had better survival than those who received neoadjuvant chemotherapy. Neoadjuvant chemotherapy should be reserved for those in whom optimal primary cytoreductive surgery is not feasible. Synopsis: In women with advanced ovarian cancer deemed to be operable, primary cytoreductive surgery leads to better long‐term survival outcomes than treatment with neoadjuvant chemotherapy.